2005
DOI: 10.3208/sandf.45.5_39
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Consolidation Settlement of Naturally Deposited Clayey Soil Under Embankment Loading

Abstract: In a naturally deposited soil foundation subject to embankment loading, a delayed settlement can often be observed after the embankment's completion, sometimes also showing acceleration over time. Frequently in such cases the soil exhibits an increase rather than a dissipation of excess pore pressure in some of its parts, a phenomenon which cannot be explained by conventional elasto-plastic consolidation theory. In this paper the possible mechanism for this kind of delayed settlement is investigated numericall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…15, the dissipation of pore pressure is delayed. As a result, large settlement continues to occur at a languid pace over a long period time in these layers (Noda et al, 2005). Figure 16 shows the deformation of the ground surface immediately after construction of the embankment and at the end of consolidation.…”
Section: Results Of Analysismentioning
confidence: 99%
“…15, the dissipation of pore pressure is delayed. As a result, large settlement continues to occur at a languid pace over a long period time in these layers (Noda et al, 2005). Figure 16 shows the deformation of the ground surface immediately after construction of the embankment and at the end of consolidation.…”
Section: Results Of Analysismentioning
confidence: 99%
“…0 =44.4 kPa. The material constants and initial conditions of the crushed mudstone specimens outlined in Table 1 are shown in Table 3 together with those of typical sand (Nakano et al, 2005) and clay (Noda et al, 2005c). The calculations were performed using the same conˆning pressure p?…”
Section: Simulation Of Triaxial Compression Test Results By the Sys Cmentioning
confidence: 99%
“…This type of delayed consolidation settlement with acceleration of settlement is actually what has been observed at the Kanda site mentioned at the beginning of this paper. Further details and the mechanism of the above phenomenon have been described in other works by various authors (for example, Noda, et al, 2005).…”
Section: Soil-water Coupled Behavior Of the Four Types Of Clay Descrimentioning
confidence: 99%
“…In previous research studies (for example, Noda et al, 2005), the authors have shown that structure dominates the mechanical characteristics of naturally deposited clays even within the skeleton structure and that the delayed consolidation settlement behavior leading to large residual settlement is particular to clays with a high degree of structure. In the current study, special attention was paid to the degree of evolution of structure in the skeleton structure of the clays and the manner in which the structures change in order to investigate how these factors aŠect the sensitivity and compression index ratios.…”
Section: Interpretation Of the Mechanical Characteristics Of Clays Sumentioning
confidence: 99%
See 1 more Smart Citation